Factors affecting the use of AI applications among educators in schools - Samuri , Norazila (Journal of Islamic, Social, Economics and Development, 2024)
Artificial intelligence is not a newly created technology, but its use is increasing after the covid-19 outbreak where there have been quite drastic developments in ICT technology and digitalization. Various AI-based platforms and applications are starting to emerge making it a necessity nowadays. The use of AI applications is also a good catalyst for the development of the education sector in Malaysia. Many studies have been conducted to identify the use of AI applications among educators. However, most of the studies involve higher education. Therefore, this study was conducted to identify the knowledge of educators related to AI applications and also the factors that influence educators in the use of AI applications in the teaching and learning process. The survey respondents consisted of educators involved as data, ICT and digitalization officers in schools around Segamat. The methodology of the study is a quantitative one that uses questionnaires and is analyzed descriptively. The findings show that educators have knowledge about AI applications, but the level of knowledge is at a moderate level. While the factors identified also showed Self-efficacy, Readiness and Literacy among educators were also at a moderate level. Efforts to disseminate the use of AI applications among educators should be implemented. In conclusion, educators need to be polished with the skills to master AI technology not only to facilitate the teaching and learning process, but also in preparation for the use of AI applications in schools in 2027.